Growth, mortality and migratory pattern of white shrimp (Litopenaeus vannamei, Crustacea, Penaeidae) in the Carretas-Pereyra coastal lagoon system, Mexico - G Rivera-Velázquez (Revista de Biología Tropical, 2008)
The growth, mortality and migration pattern of the population of Litopenaeus vannamei Boone 1931 in the Carretas-Pereyra coastal lagoon system, Mexico, were studied. The shrimp spatial distribution and abundance were analyzed in relation to salinity, water temperature, and substrate. A total of 2 669 shrimps was collected at 22 sites sampled monthly from March 2004 to August 2005. Juvenile shrimps of L. vannamei were present in the coastal lagoon system throughout the year, reaching densities from 0.001 to 0.302 ind/m². The estimated daily growth rate was 0.06 to 0.27 mm carapace length (CL). No significant seasonal differences were appreciated. Weekly total mortality (Z) was between 0.04 and 0.34. Recruits, juveniles and sub-adults displayed a bimodal distributional pattern regulated by the prevailing conditions during the dry season. The peak abundance of juvenile stages occurred in December-January and March-May. The abundance presented an inverse correlation with salinity (r=-0.42; p<0.05) and a positive correlation (r=0.44; p<0.05) with silt content. No clear correlation was distinguished for emigration size with season of the year or water temperature. Rev. Biol. Trop. 56 (2): 523-533. Epub 2008 June 30. Se estudió el crecimiento, la mortalidad y el patrón de migración del camarón Litopenaeus vannamei Boone 1931 en el sistema lagunar costero Carretas Pereyra, México. La distribución espacial y la abundancia fueron analizadas con relación a la salinidad, temperatura y substrato. De marzo de 2004 a agosto de 2005 se recolectó un total de 2669 camarones con un muestreo mensual en 22 sitios. Los jóvenes se hallaron todo el año en el sistema lagunar costero, con densidades entre 0.001 y 0.302 ind/m². La tasa de crecimiento diaria fue de 0.06 a 0.27 mm longitud del cefalotórax (CL) y no se apreciaron diferencias significativas entre estaciones. La mortalidad total (Z) semanal estuvo entre 0.04 y 0.34. Reclutas, jóvenes y subadultos presentan un patrón de distribución bimodal regulado por las condiciones prevalecientes durante la estación de estío. Los valores máximos de abundancia de los estadios juveniles se presentan en diciembre-enero y marzo-mayo. La abundancia presentó una correlación significativa inversa con la salinidad (r=-0.42; p<0.05) y positiva (r=0.44; p<0.05) con el contenido de limo. No se distinguió una clara correlación entre la talla de emigración, la estación del año y la temperatura del agua.